The The “wet sheet pack”-a Naturopathy intervention for Primary insomnia – A clinical case report - chidambaram, yogapriya; Narayanasamy, Manavalan; Rangarajan, Arunthathi; Boopalan, Deenadayalan; Akila; poornachandran, Prabu (Indian Journal of Integrative Medicine, 2022)
Insomnia is a sleep disorder characterised by difficulty falling or remaining asleep. Insomnia can be categorized into primary and secondary insomnia; however, some studies have also subcategorized it into sleep onset insomnia and sleep maintenance insomnia. Wet sheet pack is the most commonly used treatment in Naturopathy, which involves covering the whole body with a wet linen sheet followed by a woolen sheet and leaving the head uncovered. A 51 year old male presented with the complaint of primary insomnia underwent wet sheet pack treatment for seven days. After the intervention period of seven days, there was a significant improvement in PSQI, PSS, ISI and ESS. This case report shows the efficacy of wet sheet pack in management of primary insomnia.